2021
DOI: 10.1111/ijcp.14029
|View full text |Cite
|
Sign up to set email alerts
|

Personal protective equipment guidance during a global pandemic: A statistical analysis of National perceived confidence, knowledge and educational deficits amongst UK‐based doctors

Abstract: Introduction: On the 11th of March 2020, the World Health Organisation (WHO) declared a global pandemic following the upsurge of the novel coronavirus disease 2019 (COVID-19). Unprecedented global demand for personal protective equipment (PPE) resulted in restricted availability, as well as evolving guidance on use, the latter of which was complicated by conflicting guidance provided by numerous healthcare bodies. Aim: To assess perceived confidence and knowledge of PPE guidance as published by Public Health E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…The notion that ophthalmic RA/LA patients do not pose a risk of transmission to HCWs, clearly represents a lack of understanding of viral dispersion. Above notion, interestingly was also revealed in a study which showed a low perceived confidence, a deficit in knowledge and education amongst U.K. doctors across all specialities when it came to PPE [ 33 ]. As it happens, in this study, ophthalmology had the lowest scores in the knowledge based multiple choice questions.…”
Section: Discussionmentioning
confidence: 90%
“…The notion that ophthalmic RA/LA patients do not pose a risk of transmission to HCWs, clearly represents a lack of understanding of viral dispersion. Above notion, interestingly was also revealed in a study which showed a low perceived confidence, a deficit in knowledge and education amongst U.K. doctors across all specialities when it came to PPE [ 33 ]. As it happens, in this study, ophthalmology had the lowest scores in the knowledge based multiple choice questions.…”
Section: Discussionmentioning
confidence: 90%
“…Researchers widely believe that mortality would be reduced if the medical supply and PPE supply chains were protected (Swanson and Santamaria, 2021). Therefore, both the appropriate use and availability of PPE are imperative components in building a defence barrier against a highly infectious and potentially fatal virus (Yang et al , 2020; Al‐Hity et al , 2021).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Researchers widely believe that mortality would be reduced if the medical supply and PPE supply chains were protected (Swanson and Santamaria, 2021). Therefore, both the appropriate use and availability of PPE are imperative components in building a defence barrier against a highly infectious and potentially fatal virus (Yang et al, 2020;Al-Hity et al, 2021). Nathavitharana et al (2020) highlighted the potential for innovation and knowledge sharing to address PPE shortages, in turn enhancing HCWs' safety in the current COVID-19 pandemic.…”
Section: Improving and Increasing Access To Ppementioning
confidence: 99%
“… 15 , 16 Even in developed countries, HCWs reported low preparedness 17 improperly fitting personal protective equipment (PPE), 18 and low confidence due to insufficient education in PPE usage. 19 In developing countries, we saw clinics filled with suspicious patients sitting next to other patients in the same waiting area, hospital staff loosely using PPE, and HCWs coming to work even after they were tested positive for SARS-CoV-2 despite the facility’s “official” policy of home-quarantine for infected HCWs. Importantly, at the beginning of the pandemic, the mode of transmission for this new infection was uncertain which leads to delay in stringent use of masks in unprepared healthcare settings.…”
Section: Discussionmentioning
confidence: 99%